2006
DOI: 10.1038/sj.onc.1209803
|View full text |Cite
|
Sign up to set email alerts
|

A soluble ectodomain of LRIG1 inhibits cancer cell growth by attenuating basal and ligand-dependent EGFR activity

Abstract: Leucine-rich repeats and immunoglobulin-like domains-1 (LRIG1) is a transmembrane protein with an ectodomain containing 15 leucine-rich repeats (LRRs) homologous to mammalian decorin and the Drosophila kekkon1 gene. In this study, we demonstrate that a soluble ectodomain of LRIG1, containing only the LRRs, inhibits ligandindependent epidermal growth factor receptor (EGFR) activation and causes growth inhibition of A431, HeLa and MDA-468 carcinoma cells. In contrast, cells that do not express detectable levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 64 publications
1
71
1
Order By: Relevance
“…2A) (Yi et al, 2010). Consistent with the above study, a recombinant fragment of LRIG1 corresponding to the LRR domain was shown to attenuate EGFR signalling and EGFR-driven cell proliferation by acting as a high-affinity competitive inhibitor of EGF binding to the EGFR (Goldoni et al, 2007). It remains to be determined whether, and under which conditions, bioactive LRIG1 extracellular domain (LED) fragments are generated by processing of the endogenous LRIG1 protein.…”
Section: Lrig1mentioning
confidence: 59%
“…2A) (Yi et al, 2010). Consistent with the above study, a recombinant fragment of LRIG1 corresponding to the LRR domain was shown to attenuate EGFR signalling and EGFR-driven cell proliferation by acting as a high-affinity competitive inhibitor of EGF binding to the EGFR (Goldoni et al, 2007). It remains to be determined whether, and under which conditions, bioactive LRIG1 extracellular domain (LED) fragments are generated by processing of the endogenous LRIG1 protein.…”
Section: Lrig1mentioning
confidence: 59%
“…Previous evidence suggests that decorin, as a key component of the tumor stroma, interacts with various growth factors such as EGF and TGF-β and is necessary for cell migration (34,35). Furthermore, it may regulate the action of several tyrosine-kinase receptors, including the EGFR, ERK and insulin-like growth factor receptor I (36,37). Thereupon, whether similar mechanisms of ASPN play a role in tumors warrants attention.…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise mechanism by which Lrig1 destabilizes Met receptor is still unknown, it has been proposed that Lrig1 likely acts to facilitate the association of Met with the protein degradation machinery. Based on the premise that the LRR domain is the critical interacting domain between Lrig1 and EGF/ErbB receptors, Goldoni et al (2007) have recently demonstrated that a soluble ectodomain of Lrig1 containing only the LRR domain is sufficient to antagonize both ligand-independent and liganddependent EGFR activation in a non-cell-autonomous manner. In contrast to the full-length Lrig1 protein, the inhibition occurs without noticeable effects on internalization and degradation of the receptors, revealing that in mammals Lrig1 could also restricts EGFR activation by a Cbl-independent mechanism.…”
Section: Discussionmentioning
confidence: 99%